POTENTIAL OF RED FRUIT (PANDANUS CONOIDEUS CAROTEN LAMK) PAPUA BASED ON LITERATURE REVIEW - Hermelina Yosephina Burdam; Herny Simbala; Erladys Rumondor (PHARMACON, 2023)
ABSTRACRed fruit plant (Pandanus conoideus Lamk) Papua. is an endemic plant that can grows in almost all areas of Papua, from the lowlands to the highlands. Red Fruit (Pandanus conoideus Lamk,) belongs to the Pandanus family. This plant is widely available Find in Papua, Papua New Guinea, And This Research Aims To know the potential of red fruit (Pandanus conoideus Lamk) Papua based on literature review, research It Uses Qualitative Descriptive Method Aims to Draw, Describe, Explain, Explain, and answer in detail the research results. Based on literature review, red fruit has potential As Socio-Economic Value, As Traditional Medicine, Cure Cancer And tumors, HIV/Aids,High Blood Pressure, Gout, Stroke, Eye Disorders, Osteoporosis, Diabetes Mellitus, Increases Sperm Production in Men, Increases Intelligence, As a Food Source, As Antioxidant, Antidiabetic, Anti-Inflammatory Antibacterial Cardiovascular, Hypertension